The '72 in Santa Fe: political contest and an "azo" in the memory - Raina, Andrea Carla (Universidad Nacional del Litoral, 2021)
Within the context of the series of protests that took place in Santa Fe between 1969 and 1973, our goal is to analyze the different actions of the parts involved in the mobilization that until 1972 represented episodes of political contests  (McAdam, Tarrow, Tilly, 2005). Keeping the same conceptual filter of the three elements actors, actions and identities we will observe this historical moment using a qualitative methodology of the analysis of oral and written sources. We can rely on the local newspaper: El Litoral, leaflets and statements from political and trade union organizations, oral interviews and declarations obtained on occasion of the anniversary of the facts. Chronological the events that we analyze are going from: the attempt of kidnapping of the mayor Conrado Puccio by the hands of Montoneros in February 1972 and the internal impact on the political-military organization OPM; the fight called "Medio Boleto" (Half price ticket) realized by students and the active strike carried out by municipal employees involved in the union of ASOEM that caused the destitution of the mayor Conrado Puccio leaving the place to a police controller named Francisco Sgabassi and that ended with the mentioned "Manzanazo".